2012
DOI: 10.1371/journal.pone.0043550
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spermatogenesis and gr/gr Deletions Related to Y Chromosome Haplogroups in Korean Men

Abstract: Microdeletion of the Azoospermia Factor (AZF) regions in Y chromosome is a well-known genetic cause of male infertility resulting from spermatogenetic impairment. However, the partial deletions of AZFc region related to spermatogenetic impairment are controversial. In this study, we characterized partial deletion of AZFc region in Korean patients with spermatogenetic impairment and assessed whether the DAZ and CDY1 contributes to the phenotype in patients with gr/gr deletions. Total of 377 patients with azoo-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Of the 32 selected studies 14 are from descriptive [1, 2, 4, 13, 24, 27-29, 31, 32, 34-37], 08 are cross-sectional [3,5,17,18,21,25,26,33], 05 are experimental [7,12,19,20,38], 03 are case reports [22,30,39] and 02 are case-control studies [10,23]. Studies have good methodological accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 32 selected studies 14 are from descriptive [1, 2, 4, 13, 24, 27-29, 31, 32, 34-37], 08 are cross-sectional [3,5,17,18,21,25,26,33], 05 are experimental [7,12,19,20,38], 03 are case reports [22,30,39] and 02 are case-control studies [10,23]. Studies have good methodological accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have good methodological accuracy. The sample universe is quite heterogeneous, given the very design of the studies (22 case reports with 02 individuals up to 33 cross-sectional studies with 4, 441 individuals), age differences between individuals in the samples ranging from 17 years [10] to 66 years [21], as well as the origin of the patients who were: India [2,23,25,35], Brazil [3,31,34,36], China [4,10,17,18], Iran [1,7,19,21] Turkey [5,26,27] [20], Denmark [37], USA [22], england [38], Mexico [30], Serbia [28] and Venezuela [32]. Because of this situation, the data becomes divergent and the comparative analysis becomes troublesome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the Europeans and the Han Chinese have a strong association of gr/gr deletions with male infertility [11,22,27]; the American and African men with gr/gr deletions do not seem to be susceptible to azoospermia or oligozoospermia [20,21,[28][29][30]. In the Asian population, the gr/gr deletions are not associated with male infertility in the Malaysian and Japanese men; a significant association has been observed in the Korean and Chinese men [20,21,27,[31][32][33]. In the context of Indian population, the association of AZFc subdeletions and male infertility is unclear.…”
Section: Introductionmentioning
confidence: 99%